PELATIHAN ASERTIVITAS UNTUK MENURUNKAN FREKUENSI PERISTIWA BULLYING YANG DIALAMI KORBAN - Sukma Adi Galuh Amawidyati (Jurnal Psikologi Integratif, 2013)
Victim’s reaction that appears on the face of threats from the perpetrators of bullying is not assertive. The frecuency of bullying can be reduced by increasing victim’s assertion. One of the interventions to reduce bullying frequency is by giving assertion training for victim’s bullying. Subjects of this research are 13 elementary students, 4th and 5th grades that has been identifed as the victims through the bullying victim’s questionnair. This research was conducted in a quasiexperiment with the amount subject to as many as 6 students for the experiments group and 7 students for the control group. Data analysis performed using Mann Whitney U Test to compare the frequency of the victim’s bullying between the experimental group and the control group after a given treatment. The results of this study indicate that there are differences in frequency of the victim’s bullying between experimental groups and control groups (z = -3,012, p= 0,003; p<0,05).